2007
DOI: 10.1002/adfm.200700398
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Optical Study of Subphthalocyanine in a Bilayer Organic Solar Cell

Abstract: Ultra‐thin films of subphthalocyanine (SubPc) were grown onto Si/SiO2 substrates by organic molecular beam deposition and the complex refractive index has been characterized by spectroscopic ellipsometry. The peak maximum in the extinction coefficient is determined to be 1.6 at 590 nm and the dielectric constant equals 3.9 in the limit of long wavelength. These values are extraordinary high when compared to the well‐known metal‐phthalocyanines and will be beneficial for the performance in a photovoltaic cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 20 publications
(21 reference statements)
8
119
1
1
Order By: Relevance
“…Overall, η P = (4.2 ± 0.1)% is obtained for the NZEP (1:4) GHJ at 100 mWcm − 2 , compared to η P = (3.7 ± 0.1)% for an optimized mixture, and η P = (3.0 ± 0.1)% for a planar architecture (Figure 4c ). The operating parameters obtained for the planar OPV cell are consistent with those published elsewhere for the same device architecture, [ 22 ] while OPVs based on mixtures and gradients of SubPc and C 60 have not been previously examined. Based on this work, it is concluded that GHJs are an attractive approach to enhance the effi ciency of small molecule OPVs.…”
supporting
confidence: 77%
“…Overall, η P = (4.2 ± 0.1)% is obtained for the NZEP (1:4) GHJ at 100 mWcm − 2 , compared to η P = (3.7 ± 0.1)% for an optimized mixture, and η P = (3.0 ± 0.1)% for a planar architecture (Figure 4c ). The operating parameters obtained for the planar OPV cell are consistent with those published elsewhere for the same device architecture, [ 22 ] while OPVs based on mixtures and gradients of SubPc and C 60 have not been previously examined. Based on this work, it is concluded that GHJs are an attractive approach to enhance the effi ciency of small molecule OPVs.…”
supporting
confidence: 77%
“…28 Gommans et al has also reported molecular disorder for SubPc on ITO on the basis of microscopy studies. 29 Since SubPc molecules on ITO are disordered, a much lower SubPc layer thickness must be used to enhance I SC and for optimal device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Fused acenes [34][35][36][37][38][39][40][41][42][43] and several famous classes of dyes, such as phthalocyanine (Pc), [20, subphthalocyanine (SubPc), [66][67][68][69][70][71] subnaphthalocyanine (SubNc), [72,73] merocyanine (MC), [74] cyanine dyes, [75][76][77][78][79] and squaraine (SQ), [80][81][82][83] are widely used in LL vacuum deposited OPVs (Figure 2, Table 1). In 2001, Forrest and Peumans fabricated bilayer heterojunction OPVs based on CuPc and C 60 with a PCE of 3.6% under 150 mW cm −2 simulated AM1.5G illumination.…”
Section: Bilayer Structurementioning
confidence: 99%